Contribuição a análise morfométrica das regiões das bacias do Jequitinhonha e Extremo Sul, no Estado da Bahia - Christofoletti, A.; Guerra, C. E. C.; Magnavita, I. M. P.; Martins, M. R.; Tavares, A. C. (My University, 1981)
Four variables were analysed: drainage density, relief, slope angle and topographic rugosity. The maps show the spatial distribution of these variables, whose analysis allow relief classification and a more rational utilization of the environmental resources. -after English summary
Contribution to morphometrical analysis of the Jequitinhonha and Extremo-Sul basins, in Bahia State